A Case of Severe Hyperammonemic Encephalopathy Caused by Urinary Tract Infection in Obstructive Uropathy - Bo Gyung Mun; Joo Hoon Lee; Young Seo Park; Jiwon Jung (Korean Society of Pediatric Nephrology, 2021)
Hyperammonemia is mainly caused by diseases related to liver failure. However, there are also non-hepatic causes of hyperammonemia, such as urinary tract infection (UTI) due to urease-producing organisms. Urease production by these bacteria induces a hydrolysis of urinary urea into ammonia that can cross the urothelial cell membrane and diffuse into blood vessels, leading to hyperammonemia. Delayed diagnosis and treatment of hyperammonemia can lead to lethal encephalopathy that can cause brain damage and life-threatening conditions. In the presence of obstructive uropathy, UTI by urease-producing bacteria can lead to more severe hyperammonemia due to enhanced resorption of ammonia into the systemic circulation. In this report, we present a case of acute severe hyperammonemic encephalopathy leading to brain death due to accumulation of ammonia in blood caused by Morganella morganii UTI in a 10-year-old girl with cloacal anomaly, causing obstructive uropathy even after multiple corrections.